Understanding Web Search Patterns Through Exploratory Search as a Knowledge-intensive Proces - Tibau, Marcelo; Siqueira, Sean Wolfgand Matsui; Nunes, Bernardo Pereira (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2020: Anais Estendidos do XVI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2020.13131, 2020)
To better understand users’ intent, Web search engines need to transcend its information sorter utility and acquire a more relevant ability concerning semantics’ discernment. This master thesis presents the Exploratory Search KiP model, which helps clarify the reasons why a subject is searched and supports the visualization of decision criteria used for choosing a specific search result. It also introduces the ESKiP Taxonomy of Query States; a classification framework that helps to represent the structure and behavior of query reformulation in search systems. As a result, the artifacts allowed to identify Web search and query reformulation patterns. The Exploratory Search KiP model also aided to distinguish three main behaviors involved in exploratory searches: (1) The ability to increase the level of familiarity with the topic and content searched (topic familiarity); (2) The ability to control the search process itself; and (3) The ability to assess the retrieved information relevance. For further reading: [Dias 2019] at UNIRIO’s repository. A summary article from the complete work was submitted to an international Information System Journal and is currently under review